Utility of the United Kingdom National Health Services Breast Screening Program Diagnostic Protocol in Fine-needle Aspiration Cytology with Cell Block Preparation in Cases of Palpable Breast Lumps: A Reliable, Fast, and Accurate Diagnostic Method for the Assessment of Breast Lumps with Histopathologic Correlation - Pratik Bharatbhai Desai; Killol Nathubhai Desai; Nirav Sureshbhai Panchal (Wolters Kluwer Medknow Publications, 2024)
Introduction: A palpable breast lump is a common diagnostic problem for clinicians and surgeons. Fine-needle aspiration cytology (FNAC) has many advantages such as less cost, less sample processing time, less pain, less chance of hematoma, and less discomfort. FNAC with cell block preparation further increased both sensitivity and specificity by nearly 100%. With the cell block preparation, we can also use newer tests like estrogen receptor-progesterone receptor-human epidermal growth factor receptor 2. Aims: The aim of this study was to derive conclusions about the correlation, including sensitivity, specificity, positive and negative predictive values (NPVs), and the diagnostic accuracy of FNAC, with or without cell blocks, compared to the final histopathology in cases of palpable breast masses. Materials and Methods: A cross-sectional prospective study was conducted after getting approval from the Human Ethics Research Committee from January 2018 to December 2019, which included 65 patients. Patients diagnosed clinically for breast lumps who underwent diagnostic FNAC with cell block, followed by a histopathological examination at our hospital, were included in the study. Results: FNAC without cell block sensitivity, specificity, positive predictive value (PPV), NPV, efficiency rate, and diagnostic accuracy are 91.3%, 100%, 100%, 90.1%, 86.2%, and 96.5%, respectively. FNAC with cell block sensitivity, specificity, PPV, NPV, efficiency rate, and diagnostic accuracy are all 100%. All of our results beat the standard estimate. Conclusions: Fine-needle aspiration cytology is a patient-friendly, easy, reliable, repeatable, and simple diagnostic test. Whenever it is combined with cell block preparation, improves the accuracy of FNAC diagnosis which is more accurate and comparable to golden-standard biopsy with histopathology examination.